2016
DOI: 10.1038/nprot.2016.111
|View full text |Cite
|
Sign up to set email alerts
|

Surgical extraction of human dorsal root ganglia from organ donors and preparation of primary sensory neuron cultures

Abstract: Primary cultures of rodent sensory neurons are widely used to investigate the cellular and molecular mechanisms involved in pain, itch, nerve injury, and regeneration. However, translation of these preclinical findings may be greatly improved by direct validation in human tissues. We have developed an approach to extract and culture human sensory neurons in collaboration with a local organ procurement organization. Here we describe the surgical procedure for extraction of human dorsal root ganglia (hDRG) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 43 publications
1
95
0
Order By: Relevance
“…Thus, we obtained viable sensory neurons from human cadaveric donors and stimulated these cells with IL-4 (Valtcheva et al, 2016). Similar to our observations in mice (Figure 1D), we found that a subset of human sensory neurons directly responded to IL-4 (Figure 1H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we obtained viable sensory neurons from human cadaveric donors and stimulated these cells with IL-4 (Valtcheva et al, 2016). Similar to our observations in mice (Figure 1D), we found that a subset of human sensory neurons directly responded to IL-4 (Figure 1H).…”
Section: Resultsmentioning
confidence: 99%
“…After hDRG extraction, fat, dura, and connective tissues were removed as previously described (Valtcheva et al, 2016). The hDRG were subsequently stored in RNAlater (Sigma-Aldrich) at −80°C until RNA isolati on was performed.…”
Section: Star Methodsmentioning
confidence: 99%
“…and prepared as described previously [14]. Detailed protocols for the preparation and experimental use of human sensory neurons are available [47]. Briefly, the DRGs were dissected to remove connective tissue and fat.…”
Section: Methodsmentioning
confidence: 99%
“…Loss of pseudounipolarity has been described also in cultured DRG neurons from rat, mice and rabbit and have been attributed to different factors including the removal of satellite cells, which prevent dendritic formation in vivo [8], the type of GF supplementation [57] and activation of transcription factors associated to the regenerative state of dissociated neurons [58]. As in DRG cultures from other species [47, 59] postnatal bovine DRG neurons still had significant numbers of ensheathing cells attached, which does not support the removal of satellite cells as the cause for multipolarity. In contrast, neurite outgrowth, arborisation and elongation were modulated under certain GF supplementations suggesting that presence of GF is involved in neuronal morphology and loss of neuronal pseudounipolarity.…”
Section: Discussionmentioning
confidence: 99%